Morphology and Depositional Processes of a Carbonate-Filled Canyon in the Carboniferous KT-II Formation of the Eastern Precaspian Basin, Kazakhstan: Insight from 3D Seismic Data - Jiapeng Wu; Xiaodong Cheng; Shanbo Sheng; Leyuan Fan; Kai Guo; Xining Li; Wan Diao; Unmei Tai; Shutang Jin; Shengbin Zhang; Xinxin Song (Geofluids)
Canyons in carbonate depositional settings, as important elements of the source-to-sink system, remain poorly studied compared to those in siliciclastic depositional environments. The latest high-resolution three-dimensional seismic data, well logs, and core data at the eastern edge of the Precaspian Basin are used to investigate the geomorphology, infillings, and depositional process of a unique carbonate-filled canyon in the Carboniferous KT-II formation parallel to the carbonate platform, which is distinct from other slope-perpendicular canyons. The canyon has a total length of more than 52.3 km with a nearly N-S orientation and an S-shaped geometry, and the whole canyon can be divided into three segments by two knickpoints. The slope-parallel orientation of the canyon is mainly controlled by the palaeogeomorphology and reverse faults. Due to the collision of the Kazakh and European plates in the early-middle Visean (early Carboniferous), the canyon was formed in a northern tilted, elongated, and restricted palaeotopographic feature between uplifts. The development of reverse faults related to tectonic movement controlled the variations in the width of the canyon and the positions of the knickpoints. Tectonics controlled the orientation and formation of the canyon, while sedimentary processes contributed to its infilling. The well-seismic tie analysis indicated two distinct periods of the canyon fillings, Ss1 and Ss2, which were separated by a second-order sequence boundary. The lower part contained sediments supplied by both sides of the canyon through channels or gullies, and the upper part was dominated by a carbonate platform that prograded from the eastern side of the canyon. The evolution of the canyon can be subdivided into three stages. The increasing stage was mainly characterized by significant upslope erosion through headward retrogressive mass failures in the slope-parallel confined negative relief to form the canyon during the lowstand system tract of Ss1. Subsequently, in the early filling stage, the carbonate factory was productive during the highstand, and massive excess carbonate sediments were transported into the adjacent canyon by channels or gullies on both sides and deposited. The canyon was basically filled, and the morphology became much gentler. During the subsequent late filling stage, the carbonate platform was flooded again during the highstand, and the production rates of the carbonate factory greatly increased. The lateral progradation of carbonate platforms accelerated on the canyon of the early filling stage and further into the inner sag.